FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DIMODERASI PROFITABILITAS - Prihatinisah, Prihatinisah; Syahzuni, Barlia Annis (Jurnal Riset Akuntansi Politala, 2024)
Using the food and beverage sub-sector industry listed on the IDX for the 2020-2022 period, this study aims to look at the factors that can affect company value by moderating profitability. Company size, leverage, and sales growth are used as independent variables, company value is used as dependent variable, and profitability is used as a moderator. This research uses twenty companies as the population and sixty company data as research samples. The test results of this study show that company value is significantly affected by company size in a negative way, while leverage and sales growth have not been able to significantly affect company value, and profitability can’t strengthen or not moderate the relationship between company size, leverage, and sales growth to company value.